Pengaruh Pemberian Ekstrak Daun Gaharu (Aquilaria Malaccensis Lam.) Terhadap Aterosklerosis Pada Burung Puyuh Jantan (Coturnix-Coturnix Japonica) - Suhatri Suhatri; Dian Zaini Putra; Elisma Elisma (STIFARM Padang, 2014)
Study about the influence of agarwood leave’s extract (Aquilaria malaccensis Lam.) on the formation of atherosclerosis in male quail (coturnic-coturnix japonica) induced high fat feeding and prophylthiourasil. Animal experiments were grouped into 5 consisting of Group I as a negative control only given food strander, group II as a positive control and PTU given MLT groups III, IV, V given leaf extract of aloes with a dose of 100 mg / kg BW, 300 mg / kg BW, 900 mg / kg BW and, along with the MLT and PTU the extract was given orally once a day for 60 day. The doses used were 100, 300, 900 mg/kg body weight respectively. Control groups was given food standar. Result showed that the administration of the agarwood leaf extract could prevent formation of atherosclerosis in male quail significantly (P < 0.05). The optimal effect showed doses 100 mg/kg BW.